An Analysis of Maritime Alphabet Usage by Students at Politeknik Pelayaran Malahayati - Yusrah; Yuli Pera Fitria; Piping Rahadianto; Dewi Lestari Pardede; Maitri Rahmadhani (English Lecturers and Teachers Association (ELTA), 2026)
This study aims to analyze the use of the Maritime Alphabet by students of Politeknik Pelayaran Malahayati, focusing on their level of understanding, accuracy, consistency, and the challenges faced in maritime communication. This research employed a descriptive method with a mixed methods approach. The subjects of the study were 48 fourth-semester students of the Ship Electrical Engineering Study Program. Data were collected through written and oral tests, observation, and questionnaires. The results showed that the students’ ability in using the Maritime Alphabet was in the “good” category, with an average score of 76.8%. Most students (41.7%) were categorized as good, followed by very good (25%), fair (20.8%), and poor (12.5%). Based on the assessment aspects, pronunciation (72%), accuracy (78%), and fluency (70%) were also categorized as good, although pronunciation was the lowest aspect. The errors identified included mispronunciation, incorrect use of code words, lack of fluency, and the influence of the mother tongue. The questionnaire results indicated that students were aware of the importance of the Maritime Alphabet; however, they still experienced difficulties in pronunciation and lacked confidence. Therefore, practice-based learning such as simulation, role play, and pronunciation drills is needed to improve students’ maritime communication competence. Keywords: Maritime Alphabet, maritime communication, students, pronunciation